Treatment of 'cimetidine-resistant' chronic duodenal ulcers with ranitidine or cimetidine: a randomised multicentre study. Issue 10 (October 1984) - Quatrini, M; Basilisco, G; Bianchi, P A
Abstract : Forty patients with endoscopically proven persistent duodenal ulcer who had been treated for six weeks with cimetidine (1 g/day) were randomly allocated to receive a further six weeks' treatment with cimetidine (1 g/day) or ranitidine (300 mg/day). Ulcers healed in 12 of 19 patients given cimetidine (63%) and in 13 of 21 given ranitidine (62%); two patients on cimetidine and two on ranitidine dropped out. In the unhealed ulcer group the ulcer size was reduced in most patients. There was no change in basal acid output, peak acid output, plasma gastrin and pepsinogen I levels after either treatment. Clinical data, gastric function tests, and endoscopic features did not predict ulcer healing. Both treatments were effective in the relief of pain: 72% of patients with unhealed ulcers were asymptomatic at the end of the trial.